Targeting codon 158 p53-mutant cancers via the induction of p53 acetylation - Li Ren Kong (Nature Portfolio, 2020)
Codon 158 gain-of-function mutant p53 (158-mutp53) promotes tumourigenesis in lung cancer. Here, the authors show that 158-mutp53 render cancers sensitive to cisplatin and p53 acetylation agents through a mechanism where acetylated mutant p53 upregulates TRAIP and inhibits NF-ĸB signaling.